2023
DOI: 10.1039/d3ta04988d
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically spring nanofibrous and wrinkled-structured electrode for highly comfortable wearable triboelectric nanogenerators

Marjan Haghayegh,
Ran Cao,
Fatemeh Zabihi
et al.

Abstract: Fabrication of textile-based wrinkled stretchable TENGs (WS-TENGs) using spring wrinkled nylon 6/6, hierarchically wrinkled PEDOT:PSS, and wrinkled AgNWs-SWCNTs/PET-Lycra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Due to restrictions on the volume and surface area of the fibers, the electrical output of fiber-based TENGs is not high. Therefore, fabric-based TENGs have become an inevitable choice [13][14][15][16][17]. Chen et al [13] also studied the electrical output performance of three basic weaving patterns (plain, sitting, and twill) and reported that the plain pattern had the highest effective illumination area ratio of 96.1%, which delivered the highest current density of 6.35 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to restrictions on the volume and surface area of the fibers, the electrical output of fiber-based TENGs is not high. Therefore, fabric-based TENGs have become an inevitable choice [13][14][15][16][17]. Chen et al [13] also studied the electrical output performance of three basic weaving patterns (plain, sitting, and twill) and reported that the plain pattern had the highest effective illumination area ratio of 96.1%, which delivered the highest current density of 6.35 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%